Benchmark control problem for real-time hybrid simulation. (1st January 2020) - Silva, Christian E.; Gomez, Daniel; Maghareh, Amin; Dyke, Shirley J.; Spencer, Billie F.
Highlights: A collaborative initiative to enable researchers to leap forward in the topic of hybrid simulation. Focused on the design of a transfer system displacement tracking controller for RTHS. Reduced, computationally efficient model based on a realistic moment-resisting structure Physics-base models of physical components, sensor dynamics, structural variations, and noise. Able to run a RTHS simulation in real-time through the use of MATLAB Simulink Real Time Desktop functionality. Abstract: This paper presents the problem definition and guidelines for a benchmark control problem in real-time hybrid simulation for a seismically excited building, to appear in a Special Issue of Mechanical Systems and Signal Processing. Benchmark problems have been especially useful in enabling a community of researchers to leap forward on a given topic, distill the lessons learned, and identify the capabilities and limitations of various approaches. The focus here is on the design of an effective transfer system displacement tracking controller which is a commonly used approach for ensuring that interface conditions between numerical and experimental substructures are satisfied. In this study, a laboratory model of a three-story steel frame is considered as the reference structure. Realistic numerical models are developed and provided to represent the numerical and experimental substructures and the transfer system, which is comprised of hydraulic actuation, sensing instrumentation, and control implementation hardware. Experimental components are identified and provided as Simulink models, which are executed in real-time using Simulink Desktop Real-Time capability to enable realistic virtual real-time hybrid simulation. The task of each participant of the Special Issue is to design, evaluate, and report on their proposed controller approaches using the numerical models and computational codes provided. Such approaches will be assessed for robustness and performance using the provided tools. This benchmark problem is expected to further the understanding of the relative merits, as well as provide a clear basis for evaluating the performance of various control approaches and algorithms for RTHS. To illustrate some of the design challenges, a sample control strategy employing a proportional-integral (PI) controller is included, in addition to the built-in control loop of the transfer system.